Effectiveness of the personal hygiene module in increasing the knowledge of pregnant women with anemia on the dangers of worm infection - Endah Saraswati; Wahida Wahida; Malahayati Nurdjaya (Medisains)
Background: Worm infections are a common cause of anemia in pregnant women, particularly in areas with poor sanitation. While many studies have examined anemia in pregnancy, few have specifically explored the effectiveness of personal hygiene education in increasing pregnant women's knowledge of the dangers of worm infection.